66.6k views
5 votes
- a(-4-5a) - 3a(2 + a) =

User Mmla
by
4.9k points

2 Answers

3 votes

Answer:

Let's simplify step-by-step.

(−a)(−4 − 5a) − 3a(2 + a)

Distribute:

= (−a)(−4) + (−a)(−5a) + −3a^2 + −6a

= 4a + 5a^2 + −3a^2 + −6a

Combine Like Terms:

= 4a+5a^2 + −3a^2+ −6a

= (5a2+ −3a^2) + (4a + −6a)

= 2a2 + −2a

Final Answer:

= 2a^2−2a!

User George Wood
by
4.9k points
6 votes

Answer:

a = 0 or a = 1

Explanation:

-a(-4 - 5a) - 3a(2 + a) = 0

4a + 5a² - 6a - 3a² = 0

2a² - 2a = 0

2a(a - 1) = 0

2a = 0

a = 0

Or

a - 1 = 0

a - 1 + 1 = 0 + 1

a = 1

Note that a quadratic equation always has two solutions.

User Nasta
by
4.6k points